DIPLOMASI INDONESIA TERHADAP RUSIA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN MELALUI WONDERFUL INDONESIA TAHUN 2016 - 2019 - Ihne Victriwijayanti, (2022)
Tourism is one of industry that has a role in the economic development of a country because its contribute to national foreign exchange. Russia is designated as a potential market for Indonesia tourism because for number of tourist receipt, the number of tourist visits and the average length of stay per visit are quite high in Indonesia. However, the conflict between Russia and Ukraine has caused a decline in Russian outbound tourism, as well as a decrease in the number of Russian tourist visits to Indonesia. This study describes Indonesia's diplomatic efforts in increasing Russian tourist visits through Wonderful Indonesia during 2016 - 2019. The researcher use the concept of Multi-track Diplomacy, Nation Branding and Tourism to answer the research problems. The concept of Multi-track Diplomacy is used to focus research on two tracks, namely the first track (government) and the third track (business). Meanwhile, data were collected through interviews and literature studies. The results of the study indicate that diplomatic efforts carried out by state actors are holding the Indonesian Festival, Familiarization Trip (Famtrip), Promotion through the Media, and Joint Promotion with Rossiya Airlines. Meanwhile, diplomatic carried put by business actors is participating in Moscow International Tourism & Travel (MITT) and Otdykh Leisure. Keywords: Indonesia, Diplomacy, Tourism, Russia,Wonderful Indonesia